الجهود النحوية عند عبد الجليل مرتاض دراسة وصفية - سهام فطايرية (My University, 2024)
Abstract: Abdul Jalil Murtad is considered one of the grammatical figures whose efforts contributed to the development and advancement of grammar. His efforts received great attention from scholars and researchers in the field of the Arabic language. In this research, we will discuss his most important efforts in the field of Arabic grammar and the most important opinions and efforts he presented. This research is divided into Two chapters, the first chapter talks about Arabic grammar, the history of its inception, and the most important grammatical schools that arose in it, while the second chapter talks about the efforts and opinions of Abdul Jalil Murtad and some of his contributions in the field of grammar. ----------------- الملخص: يعد عبد الجليل مرتاض من بين الشخصيات النحوية التي ساهمت جهوده في تطوير النحو وتقدمه وقد حظيت جهوده باهتمام كبير من طرف العلماء والباحثين في مجال اللغة العربية وفي هذا البحث سنتناول أهم جهوده في مجال النحو العربي وأهم ما قدمه من آراء و جهود،وينقسم هذا البحث إلى فصلين حيث يتحدث الفصل الأول في النحو العربي وتاريخ نشأته وأهم المدارس النحوية التي نشأت فيه،أما الفصل الثاني يتحدث عن جهود وأراء عبد الجليل مرتاض وبعض إسهاماته في مجال النحو. ---------------------- Résumé: Abdul Jalil Murtad est considéré comme l'une des figures grammaticales dont les efforts ont contribué au développement et à l'avancement de la grammaire. Ses efforts ont reçu une grande attention de la part des universitaires et des chercheurs dans le domaine de la langue arabe. Dans cette recherche, nous discuterons de ses efforts les plus importants. le domaine de la grammaire arabe et les opinions et efforts les plus importants qu'il a présentés. Cette recherche est divisée en deux chapitres, le premier chapitre parle de la grammaire arabe, de l'histoire de sa création et des écoles grammaticales les plus importantes qui y ont surgi, tandis que le le deuxième chapitre parle des efforts et des opinions d'Abdul Jalil Murtad et de certaines de ses contributions dans le domaine de la grammaire.
Keywords: grammar; grammar schools; Abdul Jalil Murtad; النحو ،المدارس النحوية ،عبد الجليل مرتاض; grammaire; lycées